MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN ALAM (IPA) DENGAN PENERAPAN METODE DEMONSTRASI SISWA KELAS VI SD NEGERI 004 SIMPANG PULAI KECAMATAN UKUI - Simanullang, Esteruli (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This study is a class action that aims to improve learning outcomes IPA SD Negeri 004 Simpang Pulai. The background of this study is the low learning outcomes IPA. It is based on the observation of only 50% or 11 students out of 22 students who completed study results. The reasons for this are: (1) the use of a lecture by the teacher; (2) teacher-centered learning; (3) passive students, and quickly get bored and eager in the following study. Based on this the researchers want to do research through the application of the method of demonstration. The formulation of the problem in this study is whether the application of the method of demonstration can improve learning outcomes IPA SD Negeri 004 Simpang Pulai Kecamatan Ukui? The purpose of this study is to improve learning outcomes through the application of the method demosntrasi IPA. In this study, the research was conducted for two cycles. The result showed that the learning outcomes of each cycle IPA has increased. In the first cycle increased from 65 in the initial data becomes 69.25. In the second cycle increased increase with the acquisition of 74.5. Based on these results we can conclude that through the implementation of demonstration method can improve learning outcomes IPA SD Negeri 004 Simpang Pulai, Kecamatan Ukui, Pelalawan.